Effects of Zinc Supplementation on Laying Performance, Serum Chemistry and Zn Residue in Tibia Bone, Liver, Excreta and Egg Shell of Laying Hens - Idowu, O.M.O.; Ajuwon, R.O.; Oso, A.O.; Akinloye, O.A. (International Journal of Poultry Science, 2011)
The effect of different sources of Zinc (Zn) in the diets of laying birds was investigated in a 10 weeks trial. Diets were formulated to include Zinc Oxide (ZnO), Zinc Sulphate (ZnSO4), Zinc Carbonate (ZnCO3) and Zinc Proteinate (ZnP) in which Zn in each diet was supplied at 140 mgKg-1 diet. Responses measured included performance, some serum biochemistry, Zn residues in tibia bone, liver, excreta and egg shell. Significant (p